Perspectives Social Engineering and its Context for Development in Nepal (Global Journal of Human-Social Science, 2024)
Social engineering is the field of social science which study about design and influence of human societies It s concern with those social dynamics which drive on such a way that affect entire populations For social engineering social engineer needs the knowledge skills strategy techniques and ideas in relation to anthropology psychology sociology public health politics technology cybernetics and others subjects along with how these subjects influence society as a whole and the wellbeing of the individuals Donovan 2017